Percutaneous Nephrolithotomy in Children - Romano T. DeMarco (Advances in Urology)
The surgical management of pediatric stone disease has evolved significantly over the last three decades. Prior to the introduction of shockwave lithotripsy (SWL) in the 1980s, open lithotomy was the lone therapy for children with upper tract calculi. Since then, SWL has been the procedure of choice in most pediatric centers for children with large renal calculi. While other therapies such as percutaneous nephrolithotomy (PNL) were also being advanced around the same time, PNL was generally seen as a suitable therapy in adults because of the concerns for damage in the developing kidney. However, recent advances in endoscopic instrumentation and renal access techniques have led to an increase in its use in the pediatric population, particularly in those children with large upper tract stones. This paper is a review of the literature focusing on the indications, techniques, results, and complications of PNL in children with renal calculi.